{μ-6,6′-Dimethoxy-2,2′-[propane-1,3-diylbis(nitrilomethylidyne)]diphenolato}dimethanoltrinitratonickel(II)europium(III) methanol disolvate - Fei Liu (Acta Crystallographica Section E, 2009)
The title dinuclear complex, [EuNi(C19H20N2O4)(NO3)3(CH3OH)2]·2CH3OH, is isostructural with its NiII/PrIII analogue. The NiII ion is coordinated by two O atoms and two N atoms of a Schiff base ligand and by two methanol molecules, forming a slightly distorted octahedral geometry. The EuIII ion is coordinated by six O atoms from three chelating nitrate ligands and four O atoms from a Schiff base ligand, forming a distorted bicapped square-antiprismatic environment. Intermolecular O—H...O hydrogen bonds connect complexes and methanol solvent molecules.